2018
DOI: 10.48550/arxiv.1809.10340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An oracle-based projection and rescaling algorithm for linear semi-infinite feasibility problems and its application to SDP and SOCP

Masakazu Muramatsu,
Tomonari Kitahara,
Bruno F. Lourenço
et al.

Abstract: We point out that Chubanov's oracle-based algorithm for linear programming [5] can be applied almost as it is to linear semi-infinite programming (LSIP). In this note, we describe the details and prove the polynomial complexity of the algorithm based on the real computation model proposed by Blum, Shub and Smale (the BSS model) which is more suitable for floating point computation in modern computers. The adoption of the BBS model makes our description and analysis much simpler than the original one by Chubano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, once we find that P ∞ (A) and P 1,∞ (A) have no feasible solution whose minimum eigenvalue is greater than ε, the next issue is to find an x ∈ K \ intK satisfying A(x) = 0, or to find the smallest dimensional symmetric cone K min satisfying KerA ∩ intK min = ∅ and K min K. It has been shown that the smallest dimensional symmetric cone K min can be detected by using a feasible solution of D(A) [15], and several algorithms have been proposed to find a feasible solution of D(A) in a finite number of iterations [5,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, once we find that P ∞ (A) and P 1,∞ (A) have no feasible solution whose minimum eigenvalue is greater than ε, the next issue is to find an x ∈ K \ intK satisfying A(x) = 0, or to find the smallest dimensional symmetric cone K min satisfying KerA ∩ intK min = ∅ and K min K. It has been shown that the smallest dimensional symmetric cone K min can be detected by using a feasible solution of D(A) [15], and several algorithms have been proposed to find a feasible solution of D(A) in a finite number of iterations [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…Proof. The first inequality of ( 16) follows from (10) in the proof of Proposition 3.5. The second inequality is obtained by evaluating q ℓ,i (α…”
Section: Finite Termination Of the Basic Proceduresmentioning
confidence: 98%
“…[96], applied to the SDP (44). For an explicit treatment, using a substantially more complicated arguments, see [97]. We only have to notice that the number of localising constraints is polynomial in the dimension.…”
Section: Computability and Convergence Ratesmentioning
confidence: 99%